Pemanfaatan Daun Ubi Kayu Menjadi Dendeng Sebagai Makanan Alternatif Vegetarian Pengganti Protein - Firdausni, Firdausni; Anova, Inda Three (Institution for Industrial Research and Standardization of Industry - Padang, 2015)
The research on utilization of cassava leaves in making of jerky as a protein source was aimed to optimize the utilization of cassava leaves became products which were delicious, preferably and as a source of protein for vegetarians. Processing of cassava leaves became jerky was made by several stages of the process and addition of fillers, flour, and other seasoning condiment to produce a soft jerky with preferred taste. The first stage was done to get the right process and variation of flour addition, control (0%) craftsmen version, the addition of tapioca flour 25%, 50% and 75%. The results showed that the addition of flour ratio affected the levels of protein, carbohydrate and organoleptic of cassava leaves jerky. The making of cassava leaves jerky by treatment tapioca flour addition of 50% indicated optimal results with water content 2.91%, ash content 4.47%, protein 14.01%, fat content 20.15%, and crude fiber 11.10 %, and organoleptic testing for taste, color, aroma and texture were preferred. Observations storability of cassava leaves jerky with plastic packaging at room temperature was still in good condition visually for three months of storage.ABSTRAK Penelitian pemanfaatan daun ubi kayu dalam pembuatan dendeng sebagai sumber protein bertujuan untuk mengoptimalkan pemanfaatan daun ubi kayu menjadi produk olahan yang enak, disukai dan sebagai sumber protein bagi vegetarian. Pengolahan daun ubi kayu menjadi dendeng dilakukan dengan beberapa tahapan proses dan penambahan bahan pengisi, tepung, dan bumbu-bumbu yang lain sehingga dihasilkan dendeng yang empuk dengan rasa yang disukai. Tahap awal dilakukan untuk mendapatkan proses yang tepat dan variasi penambahan tepung yaitu kontrol (0%) versi pengrajin, penambahan tepung tapioka 25, 50, dan 75%. Hasil penelitian menunjukkan bahwa perbandingan penambahan tepung berpengaruh terhadap kadar protein, karbohidrat, dan organoleptik dendeng daun ubi kayu. Pembuatan dendeng daun ubi kayu dengan perlakuan penambahan tepung tapioka 50% menunjukkan hasil yang optimal dengan kadar air 2,91%, kadar abu 4,47 %, protein 14,01%, lemak 20,15%, dan serat kasar 11,10%, dan uji organoleptik rasa, warna, aroma dan tekstur disukai. Dendeng daun ubi kayu dengan kemasan plastik pada suhu ruang masih dalam kondisi baik secara visual selama tiga bulan penyimpanan.